Secondary High School Students’ Perception towards Teacher Response on EFL Writing - Fitrah Pupus Prahara; Isna Humaera (IAIN KENDARI, 2020)
This article is a qualitative study conducted to investigate students’ perceptions towards teacher’s response on EFL writing. The data collected from the students’ reflection of 12 students after receiving feedback from the teacher during three drafting times at one of senior high school in Kendari. The instruments of the study are students’ reflection, and observation sheet. The result of the study showed that students interest towards teacher response (feedback) because it has positive affect in learning English especially on EFL Writing.However,teacher responses help them in correcting their errors in writing. Students assume it can help in developing new ideas, identify error words, punctuation and also build new inspiration in writing process. The implies of the study, teacher response in learning English especially writing skill can improve students insight and knowledge to be better than before. Teacher feedback makes easier for students to know their mistakes in writing process. Key words: Error writing, Students’ reflection, Teacher response.